1995
DOI: 10.1073/pnas.92.19.8793
|View full text |Cite
|
Sign up to set email alerts
|

Transcription termination at intrinsic terminators: the role of the RNA hairpin.

Abstract: Intrinsic termination of transcription in Escherichia coli involves the formation of an RNA hairpin in the nascent RNA. This hairpin plays a central role in the release of the transcript and polymerase at intrinsic termination sites on the DNA template. We have created variants of the AtR2 terminator hairpin and examined the relationship between the structure and stability of this hairpin and the template positions and efficiencies of termination. The results were used to test the simple nucleic acid destabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
203
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(219 citation statements)
references
References 16 publications
14
203
2
Order By: Relevance
“…1A) is a small model sRNA that is induced in response to envelope stress and targets several outer membrane protein mRNAs, ultimately leading to their destabilization and degradation. As a typical sRNA, RybB is an independent, unprocessed bacterial transcription unit that consists of a 5′-terminal mRNA targeting region (23) followed by the RNA "body" that ends in a hairpin followed by a 3′-terminal oligo-U stretch as a consequence of intrinsic, Rho-independent transcription termination in bacteria (21).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1A) is a small model sRNA that is induced in response to envelope stress and targets several outer membrane protein mRNAs, ultimately leading to their destabilization and degradation. As a typical sRNA, RybB is an independent, unprocessed bacterial transcription unit that consists of a 5′-terminal mRNA targeting region (23) followed by the RNA "body" that ends in a hairpin followed by a 3′-terminal oligo-U stretch as a consequence of intrinsic, Rho-independent transcription termination in bacteria (21).…”
Section: Resultsmentioning
confidence: 99%
“…This result helps to explain the selectivity of Hfq for many sRNAs, because U-rich RNA 3′ ends are common to sRNAs as a consequence of Rho-independent transcription termination (21). Furthermore, the sequestration of the RNA 3′ hydroxyl group within Hfq suggests a protection of the respective 3′ end from enzymatic modification with important implications for Hfq function.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Inhibitory RNA polymerase-transcript interactions present a potential obstacle for continuous transcriptional cycling, with each individual cycle including transcript initiation, elongation, and termination. A number of studies have indicated that elongating E. coli RNA polymerase-transcript complexes are very stable but are destabilized at specific transcription terminators (Berlin and Yanofsky 1983;Wilson and von Hippel 1995;Mooney et al 1998;Gusarov and Nudler 1999;Yarnell and Roberts 1999). The hexameric ATP-dependent factor Rho has been shown to promote transcript release from the polymerase at certain terminators (Richardson and Conaway 1980;Shigesada and Wu 1980; for review, see Richardson 2002Richardson , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…Let ω be a hairpin consisting of a handle without bulges and a negligibly small loop, with handle length h (the number of its constituent complementary base pairs). Four experimental points are known from [52]: 7; 0.11 , 8; 0.4 , 9; 0.54 , 12; 0.2 , where the first entry in the pairs is handle length h and the last one is premature termination probability within a U-run of length N . We will now derive an equation to describe premature termination probability in the form 1 ( ) P N − , where ( ) P N is probability of the polymerase reaching the end of N bases-long U-run without a slippage event.…”
Section: Shifting Of Rna-polymerase On Dna Strandmentioning
confidence: 99%